Electrochemical performance of boron‐doped diamond films on tungsten rods with silicon interlayer. Issue 12 (28th September 2015) - Muralidhar, Pavan; Hartl, Fabian W.; Kibler, Ludwig A.; Pasquarelli, Alberto; Strehle, Steffen
Abstract : Diamond films must be deposited liquid‐tight onto conductive substrates when focusing on electrochemical applications to avoid low performance or limited reproducibility due to leakage currents, corrosion, and film delamination. Here, we report on the growth of such liquid‐tight boron‐doped nanocrystalline diamond films onto tungsten rods via silicon interlayers, resembling electrochemical electrodes. These electrodes were thoroughly studied with respect to their electrochemical performance. Cyclic voltammetry revealed for instance a broad double‐layer region of about 2–3 V and low‐background currents. The electron transfer reactions were performed with [Ru(NH3 )6 ]Cl3 and K4 [Fe(CN6 )] solutions to study the effect of electrode properties on reaction kinetics.